Winners and Losers in the Panel Stage of the WTO Dispute Settlement System - Bernard Hoekman; Henrik Horn; Petros C. Mavroidis (Research Institute of Industrial Economics (IFN), 2008)
A significant body of research has sought to examine claims that developing countries are under-represented as complainants, and/or over-represented as respondents in the WTO dispute settlement system. Most of this literature has focused on their propensity to participate, the idea being that under-representation as complainants or over representation as respondents would suggest a bias in the system. This paper provides some descriptive statistics that could shed light on a different manifestation of a bias against developing countries. It employs a dataset containing information on the legal claims made in each WTO dispute between 1995 and 2006, as well as a rough classification as to whether each specific claim was accepted or not by the respective panel. The data is used to compare the extent to propensity by which G2 countries, other industrialized countries, and developing countries have won the claims that they have made before panels.
Keywords: F13; F53; O19; 330; WTO; Dispute Settlement; Developing Countries; Winners and Losers; Internationale Schiedsgerichtsbarkeit; WTO-Regeln; Handelskonflikt; Entwicklungsländer